Individual external exposures from Nevada Test Site fallout for Utah leukemia cases and controls - Lloyd, R D; Gren, D C; Simon, S L; Wrenn, M E; Hawthorne, H A; Lotz, T M; Stevens, W; Till, J E (Health physics (1958), 1990)
External gamma-ray exposures from fallout originating at the Nevada Test Site (NTS) have been assigned to 6,507 individual subjects (1,177 leukemia cases and 5,330 control subjects) who died as Utah residents between 1952 and 1981. Leukemia cases were identified, confirmed, and classified by cell type from the Utah Cancer Registry, Utah State vital records, and medical records. Residential histories were obtained from the Deceased Membership File (DMF) of the Church of Jesus Christ of Latter-day Saints (LDS), supplemented by information from the LDS Church Census Records that were taken in 1950, 1955, and 1960-62. Control subjects were selected randomly within age strata from the DMF and were frequency-matched to the cases by age at death and for sex. Individual radiation exposures were assigned as a function of residence location and time interval for each residence during the fallout period (1951-1958) using geographic exposure data taken from the literature. Temporal distribution of exposure for subjects who resided in more than one locality or who were born or died during the fallout period was determined from data of other investigators. Calculated gamma-ray exposures for each place of residence were summed for each subject to yield the exposure to fallout from the NTS.